RENAL RESISTIVE INDEX (RRI) GUIDED BY ULTRASOUND (USG) AS A DIAGNOSTIC PREDICTOR OF ACUTE KIDNEY INJURY IN SEPSIS PATIENTS - Satria Pinanditas S; Putu Agus Surya Panji; I Made Gede Widnyana; I Wayan Suranadi; Tjahya Aryasa EM; I Made Agus Kresna Sucandra; Made Wiryana; Tjokorda Gde Agung Senapathi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
This study is an observational analytical study with a cross-sectional design conducted in the intensive care unit of RSUP Prof. Dr. I.G.N.G. Ngoerah from January 2024 until completion. The study population consisted of patients aged 18-65 years who met the criteria for sepsis diagnosis without chronic kidney disease. Data analysis was performed using SPSS version 26, including descriptive analysis, ROC curve, diagnostic test, and correlation analysis. The mean RRI at 0 hours was ±SB 0.78±0.68 cm/s for the AKI group and ±SB 0.60±0.08 cm/s for the non-AKI group. The mean RRI at 6 hours was ±SB 0.77±0.65 cm/s for the AKI group and ±SB 0.60±0.08 cm/s for the non-AKI group. The cut-off point for RRI at 0 hours was ?0.70 cm/s, with a sensitivity of 84.6%, specificity of 88.9%, accuracy of 86.4%, PPV of 91.7%, and NPV of 80%, with a relative risk of AKI of 4.58 times (95% CI 1.89-11.10; P<0.001). Meanwhile, for RRI at 6 hours, the cut-off point was also ?0.70 cm/s, with a sensitivity of 88.5%, specificity of 88.9%, accuracy of 88.6%, PPV of 92%, NPV of 84.2%, and a relative risk of AKI of 5.83 times (95% CI 2.05-16.56; P<0.001). The correlation coefficient between RRI at 0 hours and serum creatinine was r=0.380, p=0.011, while for RRI at 6 hours, it was r=0.393, p=0.008. RRI at 0 hours showed a correlation with urine production with r=-0.428, p=0.004, while for RRI at 6 hours, it was r=-0.540, p<0.001. In conclusion, RRI guided by ultrasound is a good diagnostic predictor for acute kidney injury in sepsis.